Gender Contribution in Management of Agrforestry to Household Income in Sumbermulyo Village Banyuwangi - Joko Triwanto; Lela Afinatus Saadah; Tria Wahidiah; Ali Mahmud; Febri Arif Cahyo Wibowo (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2024)
Forest management as stated in the forestry law no. 41 of 1999 it is explained that forest management must be carried out in a sustainable manner in compliance with the principles of sustainable forest management. The purpose of the study was to analyze the contribution of agroforestri management activities to household income in Sumbermulyo Village, Pesanggaran District, Banyuwangi Regency. The research was conducted in November 2020 at the coordinates of 8o32'46.3